Mistake in an electronic advertisement: Legal implication - Che Hashim, Rosmawani (UUM Press, 2019)
It is fundamental that the content of the advertisement must be free from any disputable errors. Otherwise; the owner of the advertisement shall be liable for customers claims in regard to its content. Obviously, advertisements, be it traditional or online are exposed to legal repercussion should it fails to comply with the terms as per advertised. This paper discusses the legal implications of such advertisement from a contract law perspective focusing on an electronic advertisement containing price errors. It refers to the area of mistake in contract law and highlights the common law and equitable approaches in dealing with this issue. In addition, it focuses on the Malaysian legal provisions pertaining to mistake in contract law and also the issues of unfair contract terms. This paper adopts content analysis method where the materials used were largely library-based consisting of primary and secondary data. The primary data was gathered from case-law to explain how the legal principles are applied. English cases are the major references considering their high volume of cases on contractual issues. The secondary data was based on published materials, such as textbooks, journal articles, online databases and the Internet. For analysis, this paper applied a combination method of data analysis, namely, descriptive, critical and comparative approaches. The judges statements in each case were examined carefully; highlighted loopholes, followed by rational justifications. The findings have established that notwithstanding the common law principle which recognises mistake as a vitiating factor in contract, the application of mistake as a defence in an advertisement containing price error demonstrates divergent approaches by the courts. In addition, a review on the Malaysian legal framework pertaining to this issue reveals that due protection needs to be enhanced in order to warrant justice shall be served to a customer who has an unequal bargain.